Human rights and nonviolence: Peace education in Croatia - Spajić-Vrkaš, Vedrana (Array, 2003)
The paper was written in the framework of the international EURED project (Education for Europe as Peace Education). It gives an overview of the Croatian education system and focuses on the position of peace education in the National Human Rights Education Programme. A major part of the paper refers to research on the Croatian teachers’ understanding of peace and peace education. The results confirm a great variety of teachers’ conceptual approaches in both cases. Peace is viewed in seven different ways and peace education in four. In reference to peace education, four broad categories of approaches are identified as the process approach, the competence approach, the-scope-of-influence approach and the positive vs. negative approach. Each category comprises several sub-categories. E.g. peace education understood as a process may be seen in terms of teaching (teacher-centred) or learning (student-centred) ; peace education linked to competences may be understood, solely or in combination, in terms of acquiring knowledge about peace, developing skills for peace, non-violent attitudes or peaceful behaviour or may stress peace(full) culture ; the scope-of-influence approach may differ as to whether it refers to intra-personal, interpersonal or international peace issues, etc.